J. A. Millward (1998). Beyond the pass: Economy, ethnicity, and empire in Qing Central Asia, 1759-1864. Stanford: Stanford University Press. XXII + 353 pp. - Olivieri, Chiara (Estudios de Asia y África, 2018)
J.A. Millward(1998). Beyond the pass: Economy, ethnicity, and empire in Qing Central Asia, 1759-1864. Stanford: Stanford University Press. XXII + 353 pp.